Simulasi Waktu Evakuasi Berbasis Sig Untuk Analisis Tingkat Kerentanan Penduduk Kota Padang Terhadap Bahaya Tsunami - Alkhair, Hafidz; Sutikno, Sigit; Rinaldi, Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Tsunamis are ocean waves that can be caused by earthquakes, landslides or volcanic eruptions that occur at sea either vertically or horizontally. Population of Padang city, which is more than half the population living in areas relatively close to the beach. A large of population living and indulge in the coastal of Padang city caused an increasing vulnerability of the population to the dangers of tsunami. Effective evacuation planning is an effort to minimize the possible impact of the tsunami will occur. The research methodology consists of three phases: data collection, data analysis stage of the process network analisys in ArcGIS software and the third is the analysis phase. Service area is generated using a network analyst tool. Service area in this research means that the minimum area that can be reach by evacuee before tsunami come. The results show that the shelters are not able to cover all of the areas in tsunamiprone zones. The results show that the shelters allocated by KOGAMI and DKP can not cover about 9.5% and 10.9% evacuee in tsunami prone area respectively. To overcome this, the addition of potential new shelter building must be allocated in non covered service area. Â Keywords: tsunami, evacuation, shelter, network analyst, service area